2012
DOI: 10.1089/ten.tea.2011.0300
|View full text |Cite
|
Sign up to set email alerts
|

Compaction Enhances Extracellular Matrix Content and Mechanical Properties of Tissue-Engineered Cartilaginous Constructs

Abstract: Many cell-based tissue-engineered cartilaginous constructs are mechanically softer than native tissue and have low content and abnormal proportions of extracellular matrix (ECM) constituents. We hypothesized that the load-bearing mechanical properties of cartilaginous constructs improve with the inclusion of collagen (COL) and proteoglycan (PG) during assembly. The objectives of this work were to determine (1) the effect of addition of PG, COL, or COL + PG on compressive properties of 2% agarose constructs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Although the gels did not decrease in stiffness with the incorporation of live cells, the question remains as to whether or not stiffness can eventually increase if given time for sufficient ECM production in IPNs. Han and coworkers[46] recently reported that the incorporation of sulfated GAG and type II collagen into 2% agarose constructs significantly improved their stiffness and peak stress, especially when used in combination. However, the concentration of GAG used was 2.5 mg/mL, which was much higher than the concentration of cell-produced GAG (0.11 mg/mL for the highest-performing group) in week 3 of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the gels did not decrease in stiffness with the incorporation of live cells, the question remains as to whether or not stiffness can eventually increase if given time for sufficient ECM production in IPNs. Han and coworkers[46] recently reported that the incorporation of sulfated GAG and type II collagen into 2% agarose constructs significantly improved their stiffness and peak stress, especially when used in combination. However, the concentration of GAG used was 2.5 mg/mL, which was much higher than the concentration of cell-produced GAG (0.11 mg/mL for the highest-performing group) in week 3 of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A high seeding density could provide a condensed environment favourable for cell-cell and cellmatrix interaction, but necessary for chondrogenesis. Mechanical compaction of chondrocytes was found to result in concentrated matrix content and improved compressive properties of cartilage constructs (46). A seeding density of 3x10 5 cells per 226mm 3 was found to be optimal for umbilical cord stem cells compared to 5x10 4 cells, which led to a reduced osteogenic differentiation potential (47).…”
Section: Number Of Implanted Mscsmentioning
confidence: 99%